The American influence on international commercial arbitration : doctrinal developments and discovery methods / Pedro J. Martinez-Fraga. - Martinez-Fraga, Pedro J. (Cambridge University Press, 2019)
As in its first edition, this book traces the contours of select US common law doctrinal developments concerning international commercial arbitration. This new edition supplements the foundational work contained in the first edition in order to produce a broader and deeper work. The author explores how the US common law may help bridge cross-cultural legal differences by focusing on the need to address these contrasting approaches through the nomenclature and goal of securing equality between party-autonomy and arbitrator discretion in international commercial arbitration. This book thus focuses on the common law development of arbitrator immunity, as well as the precepts of party-initiative and -autonomy forming part of the US common law discovery rubric that may contribute to promoting expediency, efficiency and transparency in international commercial arbitration proceedings. It does so by carefully analyzing, among other things, the International Bar Association (IBA) Rules on Evidence Gathering, the Prague Rules, and the role of 28 USC. §1782 in international arbitration.